The innate defensive behaviour and unconditioned fear-induced antinociception evoked by NMDA receptor activation in the medial hypothalamus are modulated by the intradiencephalic treatment with cannabidiol: the role of CB1 cannabinoid receptor - Khan, Asmat Ullah (2018)
The impacts of exogenous cannabinoids, such as the chemical constituents of Cannabis sativa like cannabidiol (CBD), on brain regions having a modest number of cannabinoid receptors, for example, the ventromedial hypothalamus, are not yet surely knew. A few researches have shown evidence that ventromedial hypothalamus (VMH) neurons play a role in modulating innate fear-induced behavioural reactions in rodents submitted to experimental models of panic attack, for example those based on prey versus wild snake confrontation paradigm. The panic attack-like state was also potentially induced in laboratory animals by N-Methyl-D-aspartate (NMDA), an excitatory amino acid, which stimulates neurons that organize defensive behavioural reactions in the central nervous system. Despite the fact that CB1 receptor-mediated endocannabinoid signaling mechanism underlies the antiaversive effect of exogenous anandamide in medial hypothalamus, there is still a lack of morphological evidence to support the distribution of CB1 receptors in the VMH. Henceforth, this study was designed to explore the specific pattern of distribution of the CB1 receptors in the VMH and, subsequently, the implication of these receptors in the endocannabinoidmodulated defensive behavioural responses followed by fear-induced antinociception evoked by NMDA microinjected in the VMH. A stainless steel guide-cannula was embedded in the rodent\'s brain coordinated towards VMH by means of stareotaxic surgery. Three different doses of cannabidiol (CBD) were microinjected in the VMH. The most effective dose was used after the pretreatment with the CB1 receptor-antagonist AM251, followed by NMDA microinjection in the VMH. The outcomes demonstrated that the defensive behavioural responses evoked in response to intra-VMH administration of NMDA (6 nmol) were decreased by intra-hypothalamic microinjections of CBD at the highest dose (100 nmol).These effects, however, were blocked by the administration of the CB1 receptor-antagonist AM251 (100 pmol) in the VMH. In addition, the fear-induced antinociception elicited by VMH chemical stimulation diminished after the VMH treatment with CBD, an effect reversed by the intra-diencephalic pretreatment with AM251. These findings suggested that CBD causes panicolytic-like effects when administered in the VMH, and that antiaversive effect recruits the CB1 receptor-endocannabinoid signaling mechanism in VMH.